Framework Administered Account for Selected Fund Activities : East Africa Regional Technical Assistance Center (AFRITAC East) Subaccount. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
In March 2009, the Fund established a new Framework Administered Account to administer external financial resources for selected Fund activities (the 'SFA Instrument'). The financing of activities under the terms of the SFA Instrument is implemented through the establishment and operation of a subaccount within the SFA. The subaccount for the East Africa Regional Technical Assistance Center (AFRITAC East) would be the third one under the SFA. This paper requests Executive Board approval to establish the AFRITAC East subaccount under the terms of the SFA Instrument.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet